Irradiación gamma: conceptos básicos, aplicación y efectos en mango (Mangifera Indica) y pimientos (Capsicum spp.) - Juárez Calderón, Luis Alberto (2024)
The search for new technologies in food preservation is allowing the application of some not so common techniques. In the present research, an intensive review of gamma irradiation and its application in foods, particularly in minimally processed peppers (Capsicum spp.) or those converted to fresh-cut products, has been carried out. The information found indicated that gamma irradiation is an emerging technique that serves for the inactivation of pathogenic microorganisms and sometimes increases the nutritional value of foods, but it can also have negative effects depending on the dose applied to the food. The results concerning the effect on mangoes (Mangifera Indica) indicated that it negatively affects their organoleptic characteristics such as color, texture and firmness at doses between 700 Gy and 1 KGy and onwards. With respect to peppers of different varieties, changes were observed in their nutritional characteristics: in piquillo peppers, total phenolics increase and vitamin C content decreases, in yellow California peppers, phenolic compounds increase and in green peppers, chlorophyll content decreases, losing color.